Is There Any Equal Opportunity Approach in Latin America? A Systematic Review 2014-2024 - Carbajal Camberos, Juan Pablo (ETHICS IN PROGRESS, 2025)
This paper presents the results of a systematic literature review examining the evolution of contemporary Theories of Justice, Egalitarianism, and the Principle of Equality of Opportunity in Latin American countries from 2014 to 2024. It seeks to contribute perspectives from the Global South to the philosophical field, thereby enriching the dialogue on how egalitarian justice operates across diverse contexts. The study used three academic databases: Scopus, Web of Science, and Google Scholar. A total of 864 articles were initially identified, and after applying the PRISMA methodology, 64 papers were selected according to the established criteria. The analysis reveals that these works reflect a distinctly Latin American approach characterized by: Intrinsic Pluralist Egalitarianism (relational-distributive), Decolonial and Feminist Theoretical Influence, and Pragmatic Equality of Opportunity.